Shoulder strength and conditioning
Effects Of Repetitive Throwing On Shoulder Range Of Motion Mahan CE, Houglum PA, Arnold BL: University of Virginia, Charlottesville, VA Concentric Shoulder External To Internal Strength Ratios For Collegiate Athletes And Non-Athletes Smedley B, Noffal G, Kersey R, Max J: California State University-Fullerton, Fullerton, CA Differences In Lateral Scapular Slide In Overhead And Non-Overhead Athletes, And Non-Athletes Good AN, Buchanan KR, Boswell LL, Perrin DH, Gansneder BM: University of Virginia, Charlottesville, VA A Comparison Of The Three-Dimensional Characteristics Of A Full-Effort Overhand Throw And The Throwing Motions Involved In A Rehabilitative Throwing Program Norkus SA, Armstrong CW, Campbell BM, Swartz EE, Tucker WS, Rankin JM, Skelly WA: University of Toledo, Toledo, OH Patterns Of Scapular Positioning During Humeral Elevation In Healthy Shoulders Timmons MK, Borsa PA, Sauers EL: Shoulder Kinematics Laboratory, Division of Kinesiology, University of Michigan, Ann Arbor, MI, and Department of Sports Health Care, Arizona School of Health Sciences, Phoenix, AZ Isometric Shoulder Rotator Strength Characteristics Of High School Swimmers Throughout A Competitive Swim Season Ramsi M, Swanik KA, Mattacola CG, Swanik CB: Biokinetics Research Laboratory, Athletic Training Division, Temple University, Philadelphia, PA In-Season Surgical Tubing Strengthening Program Improves Throwing Velocity Among High School Pitchers Baheti ND, Harter RA: Sports Medicine Research Laboratory, Oregon State University, Corvallis, OR Effect Of Scapular Plane Angle On Shoulder Internal and External Rotation Strength Tanaka S, Ingersoll CD, Cordova ML, Sandrey MA: Athletic Training Department, Indiana State University, Terre Haute, IN